ANALISIS PENURUNAN TIMBUNAN BADAN JALAN PADA TANAH LEMPUNG LUNAK - Nyoman Suaryana (Jurnal Jalan-Jembatan, 2008)
Over the past many years the well-known theory of consolidation developed by Terzaghi, directly or in extended form, has been usually applied to analyze the time rate of settlement and excess pore water pressure dissipation arising from loading a soft soil. In recent reviews, it has been observed that success in predicting magnitudes and rate of settlement using Terzaghi’s theory from different field cases ranging from excellent to poor. The anomalous behavior can be explained in terms of such factors as the non-linear relationship between void-ratio and logarithm of effective stress, and changes in permeability and compressibility as load increases. In this studys, a computer program has been developed to consider two dimensional consolidation of stratified cohesive soils under embankment loading, the theory used : i.e. 1) Terzaghi-Rendulic theory and 2) non linear theory. Three case histories were presented, i.e. Trial embankment at Juru, Malaysia, Muar Flats, Malaysia and Tickton, UK. The results indicate that predictedvalues using non-linear theory for both settlement and pore water pressure dissipation close to the field measured values comparing to those using the Terzaghi-Rendulic theory. Keywords : soft clay consolidation, non-linear theory, Terzaghi-Rendulic theory